2006
DOI: 10.1172/jci28621
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid amide hydrolase deficiency limits early pregnancy events

Abstract: Synchronized preimplantation embryo development and passage through the oviduct into the uterus are prerequisites for implantation, dysregulation of which often leads to pregnancy failure in women. Cannabinoid/ endocannabinoid signaling via cannabinoid receptor CB1 is known to influence early pregnancy. Here we provide evidence that a critical balance between anandamide synthesis by N-acylphosphatidylethanolamine-selective phospholipase D (NAPE-PLD) and its degradation by fatty acid amide hydrolase (FAAH) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 56 publications
5
104
1
2
Order By: Relevance
“…Moreover, WT mice exposed to Δ 9 -THC or methanandamide (a stable AEA analogue) phenocopied Faah −/− mice with oviductal transport defects, which was rescued by CNR1 antagonist treatment. 44 All these results lend additional support to the hypothesis that either higher or lower endocannabinoid signaling adversely affects female reproduction in mice since normal oviductal transportation is disrupted in either absence of cannabinoid signaling in Cnr1 −/− mice or high cannabinoid signaling in Faah −/− mice. Previous studies have shown that it is the wave of oviductal muscle movement that sends the embryos into the uterus and that this movement is regulated by the sympathetic nervous system.…”
Section: Endocannabinoid Signaling In the Mousesupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, WT mice exposed to Δ 9 -THC or methanandamide (a stable AEA analogue) phenocopied Faah −/− mice with oviductal transport defects, which was rescued by CNR1 antagonist treatment. 44 All these results lend additional support to the hypothesis that either higher or lower endocannabinoid signaling adversely affects female reproduction in mice since normal oviductal transportation is disrupted in either absence of cannabinoid signaling in Cnr1 −/− mice or high cannabinoid signaling in Faah −/− mice. Previous studies have shown that it is the wave of oviductal muscle movement that sends the embryos into the uterus and that this movement is regulated by the sympathetic nervous system.…”
Section: Endocannabinoid Signaling In the Mousesupporting
confidence: 54%
“…Similarly, circular muscles maintained a relaxation phase in Faah −/− mice, where AEA levels were higher than in WT mice. 44 In conclusion, either higher or silenced endocannabinoid signaling disrupts the balance between muscular contraction and relaxation, impairs normal wave movement through the oviduct, and consequently derails normal oviductal transport of embryos.…”
Section: Endocannabinoid Signaling In the Mousementioning
confidence: 99%
“…Endocannabinoid signaling plays a key role in regulating female fertility. We previously showed that mice missing Faah or Cnr1 have impaired preimplantation embryo development and oviductal embryo transport (18,24). Nearly 30% of embryos are trapped in the oviducts of these mutant mice.…”
Section: Resultsmentioning
confidence: 99%
“…3 Increased FAAH expression and lower anandamide levels have been demonstrated at the implantation site and low FAAH expression and high anandamide levels at the interimplantation site prior to successful implantation. 2 Levels of FAAH in peripheral blood mononuclear cells from uncomplicated early pregnancies were significantly lower in women who subsequently miscarried. 4 In women undergoing in vitro fertilization and embryo transfer, high plasma anandamide level at 6 weeks after embryo transfer was associated with failure to achieve an ongoing pregnancy.…”
mentioning
confidence: 90%
“…1 Recent animal studies suggest that the endocannabinoid anandamide (N-arachidonoyl-ethanolamine) is critical for both the synchronous development of the blastocyst and the endometrium in preparation for implantation, with low anandamide levels essential for successful implantation. 2 Plasma anandamide levels are regulated by fatty acid amide hydrolase (FAAH), the enzyme (up-regulated by progesterone) that metabolizes anandamide into arachidonic acid and ethanolamine. 3 Increased FAAH expression and lower anandamide levels have been demonstrated at the implantation site and low FAAH expression and high anandamide levels at the interimplantation site prior to successful implantation.…”
mentioning
confidence: 99%